(NpSIHOLOG)QÆ^NÆ TA SOCÆOÆSTORI^NÆ KOMPONENTI MUZI^NO(B-(NSCENÆ^NOÇ VITTÃTWOR^OSTÆ sOLOMÆÇ kRU[ELXNICXKOÇ (B:s)E (NDISERTAC)QÆQ NA ZDOBUTTQ NAUKOWOGO STUPENQ KANDIDATA MISTECTWOZNAWSTWA (B/s)E - (NkOMAREWI^(B, )Qæ(NWANNA lEONÆDÆWNA(B,s)E; (NkIQNOWSXKA(B, (Nl@BOW oLEKSANDR)QÆWNA(B,s)E; (Nm)QÆNÆSTERSTWO KULXTURI uKRAÇNIs)E; (NlXW)QÆWSXKA NACÆONALXNA MUZI^NA AKADEMÆQ ÆMENÆ m(B. (Nw(B. (NlISENKAs)E ((NlXW)QÆW(B,s)E, 2016)
(Nw DISERTAC)QÆÇ Z(B'(NQSOWANÆ TA UZAGALXNENÆ PSIHOLOGÆ^NÆ(B, (NSUSPÆLXNÆ(B, (NNACÆONALXNO(B-(NMENTALXNÆ TA ÆSTORI^NÆ SKLADOWÆ VITTÃTWOR^OSTÆ sOLOMÆÇ kRU[ELXNICXKOÇ(B.s)E
(Nb)QÆBLÆOGR(B.: (NS(B. 150-169s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NkRU[ELXNICXKA s(B. (Na(B.s; (NmUZIKAs -- (NoPERNE MISTECTWOs -- (NsCEN)QÆ^ENE MISTECTWOs)E